Total quality management practices in Islamic banking system: a study in banking sector of Malaysia - Islam, Mohd Aminul; Hossin, M.M (ENRICHED Publications, 2017)
Total quality management is evolving over time and like many other industries, it is practicing by Islamic banks in Malaysia. The objective of this study is to identify the need of TQM in Islamic banking system, to understand its role and challenges for implementation. We have used qualitative research methods by taking five interviews and observations of three banks that follow Islamic Shariah principles, located in International Islamic University Malaysia. The findings from this research were comprehensive. TQM significantly impact the performance of Islamic banking system by enhancing customer satisfaction with limited challenges. Continuous improvement of processes involves training of employees. More data can be collected from other banks in available course of time if permits. Research findings can be helpful for those banks who did not implement TQM yet.